Stelis Swartz - Karremans Lok, Adam Philip (2022)
Stelis Sw. is the most diverse genus in the Pleurothallidinae subtribe with over 1240 species recognized today. With 107 species recorded in Costa Rica, Stelis is rivaled in numbers only by Epidendrum L. and Lepanthes Sw. However, we expect this diversity to be highly underestimated given the ubiquitous nature and the vast number of unidentified specimens belonging to the genus in botanical collections. Species of Stelis are not only diverse, they are also extremely widespread ecologically, growing mostly as epiphytes in virtually every habitat found in the country.